2020
DOI: 10.1007/s00284-020-02243-5
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus Cell Surface Proteins Involved in Interaction with Mucus and Extracellular Matrix Components

Abstract: The gut microbiota is a complex microbial ecosystem where bacteria, through mutual interactions, cooperate in maintaining of wellbeing and health. Lactobacilli are among the most important constituents of human and animal intestinal microbiota and include many probiotic strains. Their presence ensures protection from invasion of pathogens, as well as stimulation of the immune system and protection of the intestinal flora, often exerted through the ability to interact with mucus and extracellular matrix compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 100 publications
1
37
0
Order By: Relevance
“…Consistent with other reports, lactobacilli are dominant in the ileum at the genus level [ 39 , 40 ]. Several studies have repeatedly shown that lactobacilli , as the most important microbiota in animal intestines, have various biochemical functions, including in the protection of the integrity of the intestinal mucosal, the invasion of pathogens, and stimulation of the immune system [ 41 , 42 ]. Many probiotic strains of lactobacilli have been widely used in poultry production [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other reports, lactobacilli are dominant in the ileum at the genus level [ 39 , 40 ]. Several studies have repeatedly shown that lactobacilli , as the most important microbiota in animal intestines, have various biochemical functions, including in the protection of the integrity of the intestinal mucosal, the invasion of pathogens, and stimulation of the immune system [ 41 , 42 ]. Many probiotic strains of lactobacilli have been widely used in poultry production [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…One commonly used immortalized endocervical epithelial cell line is generally considered not to produce mucus (End1) while another does (A2EN) ( Radtke et al., 2012 ). Collection of cervical mucus and assessment of physical and biochemical properties in vitro , or co-culture of microbes and mucus or mucins have provided additional insight ( Muscariello et al., 2020 ). The source and processing of mucins for use in these experiments is important to retain their in vivo biologic activity ( Kavanaugh et al., 2014 ; Wheeler et al., 2019 ).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…All the complete L. plantarum genomes along with DKL3 and JGR2 were subjected to BLAST with 15 cell adhesionrelated protein sequences 38 (Table S3) using BLASTp with an E-value, % query coverage, and % identity thresholds of 1E-10, 70%, and 50%, respectively. These genomes were also annotated using dbCAN2.0 for the identi cation of the carbohydrate-active enzymes as described on CAZy 39,40 .…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…to be required for colonization in the host 38 . The genomes of DKL3 and JGR2 were searched for the presence of genes encoding such proteins 38 (Table S3).…”
Section: Adhesion To Human Intestinal Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation